Flow cytometry in the diagnosis and prognosis of canine lymphoma and leukemia - Wiseman, Michael, author; Avery, Paul R., advisor; Morley, Paul S., committee member; Olver, Christine S., committee member (Colorado State University. Libraries, 2010)
Chapter one explores new markers of prognosis for canine lymphoma by using flow cytometry of lymph node aspirates. Data from one hundred and sixty dogs with confirmed multicentric B-cell lymphoma were used to test the hypothesis that poor patient outcome could be predicted by tumor cells expressing a low level of class II major histocompatibility complex (MHC), a large cell size on flow cytometry, and expression of stem cell antigen CD34. Poor outcome was defined by a reduced first remission time (FRT) and/or overall survival time (ST). In this two-part retrospective study, two-thirds of patients (modeling group, n=106) were randomly selected to construct a multi-variable statistical model to identify test variables which showed a significant association with poor patient outcome. The second part validated the statistical associations by using the model to predict outcome on the remaining one-third of patients (validation group, n=54), whose clinical outcomes were known. Results found that class II MHC expression was the most significant prognostic marker identified in both uni-variable and multi-variable analysis. Treatment type also influenced probabilities of both relapse and mortality, while cell size and patient age only impacted mortality. CD34 expression did not influence outcome. Overall, the constructed model performed variably in predicting the validation group's outcome at the 180 day post-treatment time point. Immunophenotyping of lymph node aspirates via flow cytometry is useful in the confirmation and prognosis of canine lymphoma. Reduced class II MHC expression is correlated with a reduced patient FRT and ST, and it may suggest a means by which tumor cells evade immune detection. Chapter two describes a retrospective pilot study that assesses the immunologic, morphologic, and clinical features of canine CD34+ acute leukemias. Flow cytometry data, CBC and blood film evaluation from 11 dogs with CD34+ acute leukemia were compared to 11 dogs with CD34- acute leukemia in order to identify qualitative differences in terms of cellular morphology, degree of presenting cytopenias, patient signalment and survival. The CD34+ dogs were classified as follows: 8 had acute undifferentiated leukemia (AUL), 2 had undefined acute lymphoblastic leukemia (CD3-CD5+ undefined ALL) and 1 had acute myeloid leukemia (AML). CD34- dogs were classified as follows: 1 AUL, 1 CD3-CD5+ undefined ALL, 5 T-cell ALL, and 4 B-cell ALL. Most dogs were affected with single or bicytopenia, with both groups having a similar frequency of anemia and thrombocytopenia. CD34+ dogs had significantly more severe anemia and were significantly younger at time of diagnosis. The groups did not differ in total white blood count, blast cell count, flow cytometry cell size, or survival time. CD34+ and CD34- leukemic cells subjectively did not differ greatly in their morphologic appearances. Flow cytometry of peripheral blood enhances the traditional morphologic-based classification of acute leukemias, particularly when CD34 antigen is expressed. Some acute leukemias may not be accurately classified as such when only a morphologic evaluation of peripheral blood is performed.
Keywords: lymphoma; CD34; immunophenotype; flow cytometry; canine; leukemia; Flow cytometry -- Diagnostic use; B cells -- Tumors -- Prognosis; Dogs -- Diseases; CD antigens; Leukemia